ANALISIS STRUKTURALISME DINAMIK PADA CERPEN “ROBOHNYA SURAU KAMI” KARYA A.A. NAVIS - Andini, Hollysa (LPPM Institut Pendidikan Nusantara Global, 2021)
The purpose of this study was to determine the dynamic structuralism in the short story entitled